2007
DOI: 10.1101/gr.7144908
|View full text |Cite
|
Sign up to set email alerts
|

Wolbachiagenome integrated in an insect chromosome: Evolution and fate of laterally transferred endosymbiont genes

Abstract: Recent accumulation of microbial genome data has demonstrated that lateral gene transfers constitute an important and universal evolutionary process in prokaryotes, while those in multicellular eukaryotes are still regarded as unusual, except for endosymbiotic gene transfers from mitochondria and plastids. Here we thoroughly investigated the bacterial genes derived from a Wolbachia endosymbiont on the nuclear genome of the beetle Callosobruchus chinensis. Exhaustive PCR detection and Southern blot analysis sug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
157
1
6

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 180 publications
(168 citation statements)
references
References 37 publications
4
157
1
6
Order By: Relevance
“…30% with respect to the gene repertoire) have been found in the genome of the bean beetle Callosobruchus chinensis. However, although a low transcriptional level could be detected, most of the genes in these transferred fragments have been pseudogenized [49,50].…”
Section: Horizontal Gene Transfer In Arthropodsmentioning
confidence: 99%
“…30% with respect to the gene repertoire) have been found in the genome of the bean beetle Callosobruchus chinensis. However, although a low transcriptional level could be detected, most of the genes in these transferred fragments have been pseudogenized [49,50].…”
Section: Horizontal Gene Transfer In Arthropodsmentioning
confidence: 99%
“…(g) Phylogenetic affinity to laterally transferred Wolbachia genes in C. chinensis Of the 31 Wolbachia genes detected from M. alternatus, 11 genes ( fabF, gltP, mpp2, ftsH, gyrA, qor, ftsZ, hslU, thy1, priN and petA) were also found in laterally transferred Wolbachia genes from the adzuki bean beetle C. chinensis (Nikoh et al 2008). Molecular phylogenetic analyses revealed that, as with the ftsZ gene alone (figure 1), the Wolbachia genes from M. alternatus consistently exhibited phylogenetic affinity to the laterally transferred Wolbachia genes in C. chinensis (figure S2 in the supplementary electronic material).…”
Section: (D) Biparental and Mendelian Inheritance Of Wolbachia Genementioning
confidence: 99%
“…The constant and intimate contact between the eukaryotic host cells and inhabiting bacterial associates may predispose the exchange of genetic materials between the partners. Among insects and nematodes, Wolbachia endosymbionts have been identified as a major source of laterally transferred genes in their genomes (Kondo et al 2002b;Fenn et al 2006;Dunning Hotopp et al 2007;Nikoh et al 2008;Klasson et al 2009;Nikoh & Nakabachi 2009;Woolfit et al 2009). …”
Section: Introductionmentioning
confidence: 99%
“…LGT of fragments of the Wolbachia genome (total size approximately 1.2 Mb), ranging from 500 base pairs to more than 1 Mb, have been observed in many invertebrates, including beetles (Nikoh et al, 2008), grasshoppers (Funkhouser-Jones, 2015;Toribio-Fernández et al, 2017), wasps (Dunning-Hotopp et al, 2007), fruit flies (Dunning-Hotopp et al, 2007;Klasson et al, 2014;Choi, Bubnell and Aquadro, 2015;Morrow et al, 2015), tsetse flies (Brelsfoard et al, 2014;Nakao et al, 2016), butterflies and moths , kissing bugs (Mesquita et al, 2015), mosquitoes (Klasson et al, 2009;Hou et al, 2014), filarial nematodes (Fenn et al, 2006;Dunning-Hotopp et al, 2007;Keroack et al, 2016) and spiders (Baldo et al, 2008).…”
Section: Uses Of Wolbachia In Control Methodsmentioning
confidence: 99%